Finnsheep and Romanov comparative performances obtained under the same management conditions in Spain - Ortiz, M. Valls (Agricultural and Food Science, 1988)
Twenty-five Finnsheep (F) ewes and five F rams imported from Finland, ten Romanov (R) females and six R males and their offspring up to about 50 ewes from each breed were kept together in Zaragoza (41º 43’ LN; min. temp. —5º C, max. temp. 40 º C) over seven years. The animals were kept indoors and the reproduction system was three lambings in two years, with matings in February, June and October. Oestruses were synchronized without using PMSG so as to group lambings. As a whole, the adaptation of R was better than that of F owing to a higher incidence of pneumonic problems in this breed (36 % vs 81 % mortality between 7 and 150 days of age and 31 % vs 45 % mortality in adult ewes were caused by pneumonia). Fertility was lower in F than in R for one year old ewes (54 % vs 81 %) and for June matings (52 % vs 80 %), but it did not differ in the rest of the year (78 % vs 83 %). The average prolificacy was 1,93 vs 2,59 for F and R respectively. Total lamb mortality up to 150 days of age was high and similar in both breeds, 38 % vs 42 %, but more R than F lambs diet at birth, (16 % vs 11 %), while after the first week the mortality percentage was higher (15 % vs 22 %) in F lambs. The weights of R were higher than those of F both in the growth period of lambs (20,5 ± 0,4 kg vs 18,8+ 0,4 kg at 90 days), and in the adult stage, where the weightof 4-year-old females was 59,2±0,9 vs 56,0± 1,1 kg.